Prevention of Hypothermia of Low Birth Infants Using The Kangaroo Method - Anna Alisjahbana; Ali Usman; Suzi lrawaty; Atte Triyati (Paediatrica Indonesiana, 1998)
Hypothermia is a common problem in neonates and an important contributory factor to neonatal mortality and morbidity. The results of an evaluation involving several health facilities and health personnel showed that thermal control practices were frequently inadequate in the following areas: ensuring a warm environment at the time of delivery, initiation of breastfeeding and contact with mother, bathing, checking the baby's temperature, thermal protection of low birth weight babies, and care during transportation. During kangaroo method (K-M) the infant is in skin to skin contact with the mother. A pilot study conducted on LBW infants discharged from the General Hospital in Bandung, and follow-up for 4 consecutive weeks showed the skin temperature to be well maintained. Weight increase was more stable compared to the control group and there were no re-hospitalization within the observation period. K-M has a simple and natural appeal, cold stress can be avoided; perhaps the most important benefit of K-M is improvement of lactation. In developing countries especially rural areas, temperature regulation and maintenance of lactation using K-M may be lifesaving for very low birth infants.